Comorbidity of disruptive behavioral disorders and attention-deficit hyperactivity disorder—Indicator of severity in problematic behavior?. (August 2013) - Nordström, Tanja; Ebeling, Hanna; Hurtig, Tuula; Rodriguez, Alina; Savolainen, Jukka; Moilanen, Irma; Taanila, Anja
Abstract Background: Disruptive behavioral disorders (DBD) and attention-deficit hyperactivity disorder (ADHD) are both characterized by certain patterns of misbehavior among adolescents. Aims: The aim of this study was to examine how the comorbidity of DBD and ADHD affects in misbehavior among adolescents. Methods: A total of 158 adolescents aged 16–18 years, from a subsample of the Northern Finland Birth Cohort 1986 (NFBC 1986), were interviewed with the Finnish translation of the semi-structured Schedule for Affective Disorders and Schizophrenia for School-Age Children—Present and Lifetime (K-SADS-PL) in order to obtain DBD, including conduct disorder (CD) and oppositional defiant disorder (ODD), and ADHD diagnoses. The structure of the CD symptoms, obtained from the K-SADS-PL, was compared with the previously formed model about the development of the problematic behavior. The severity of the CD symptoms was compared with adolescents diagnosed with only DBD, only ADHD and with both DBD and ADHD. Also, the associations with other psychiatric disorders diagnosed at age 16 were evaluated. Results: The boys in the study sample were diagnosed with ADHD or with comorbid DBD and ADHD more often than girls. The severity of CD symptoms was statistically significantly associated with the comorbid DBD and ADHD group. The adolescents diagnosed with comorbid DBD and ADHD had an increased risk for anxiety disorders, depressive disorders and substance abuse disorders. Conclusions: The comorbidity of DBD and ADHD seems to indicate the severity of CD symptoms. Clinical implications: The comorbidity between DBD and ADHD should be considered in clinical practice because it could indicate more serious problematic behavior than pure disorders alone.